Flyer: "Revival Meetings! At the Assembly of God Church, Bayard, Nebraska, beginning Sunday, November 9," [circa 1924] - Carmichael, Richard, Rev., 1900-1960; Carmichael, Adele, Rev., 1902-2003 (My University, 1924)
Flyer: "Revival Meetings! At the Assembly of God Church, Bayard, Nebraska, beginning Sunday, November 9," [circa 1924].
1 PDF document, 1 page. Flyer: "Revival Meetings! At the Assembly of God Church, Bayard, Nebraska, beginning Sunday, November 9, [circa 1924]". Note: This event would have occurred before 1924. Adele and Richard Carmichael: Series 2, Box 1, Folder 1, ephemera Bethel church years. MS/150/9 Valdosta State University Archives and Special Collections.
Keywords: Advertising fliers; Assembly of God (Bayard, Neb.); Bayard (Neb.); Evangelists; New Age ministers; Pentecostalism; Women evangelists; Evangelistic work; Church musicians; Clergy; Photographs